Pelatihan Pembuatan Video Interaktif Serta Penggunaan Google Classroom Dalam Pembelajaran Jarak Jauh (PJJ) - Hennie Tuhuteru; Moh. Ramli Sukunawatan; Yeris Almendo Iwane (Universitas Lancang Kuning, 2021)
SMTK Teon Nila Serua is one of the schools which its learning process are affected by the Covid-19 pandemic. This school does not have its own Learning Management System so an alternative is made for students to study in groups in their respective villages and will be visited by the teacher every month. Several problems were found such as unattractive material in the form of a text module, students’ difficulty in understanding hardcopy teaching materials, and reprinted teaching materials that should be taken by all students living quite far from the school location. The purpose of this training is to overcome these problems with training on making interactive videos and training on the use of Google Classroom for teachers and students. Activities are carried out in four stages, namely the preparation stage, implementation stage, evaluation, and program sustainability. This activity has been carried out well where there has been an increase in participants' understanding in making interactive videos by 95% and the use of Google Classroom in simulating the teaching and learning process by 90%.